2020
DOI: 10.2334/josnusd.18-0481
|View full text |Cite
|
Sign up to set email alerts
|

Newly developed mastication activity reduction procedure rapidly induces abnormal atrophic change of the mandibular condyle in young and elder experimental animal models

Abstract: This study was performed to develop a new rat model of reduced masticatory activity in order to assess the effect of this reduction on the morphology of the temporomandibular joint (TMJ) over time. Female rats were used, and ovariectomy was performed to simulate aged/ postmenopausal status. Twenty-four SD rats aged 6 weeks were divided into four groups: ovariectomy/sham procedure (Ov/S); ovariectomy/ reduced masticatory activity (Ov/RMA); non-Ov/S (NO/S); and non-Ov/ RMA (NO/RMA). The RMA procedure involved gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Many included studies investigated how the loss of ovarian hormones and reduced masticatory activity negatively impacted the mandible and TMJ. 38–42 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many included studies investigated how the loss of ovarian hormones and reduced masticatory activity negatively impacted the mandible and TMJ. 38–42 …”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, studies that investigated the relationship between menopause and these structures focused on how the loss of ovarian hormones and reduced masticatory activity negatively impacted mandibular structures, rather than how changes in these bony structures result in disturbances in mastication. 38–42 , 62–66 Therefore, a clear gap in the literature exists regarding how menopause may negatively impact mastication.…”
Section: Discussionmentioning
confidence: 99%
“…Since that region is encompassed by the periodontal ligament, the different mastication forces experienced here could lead to different bone remodeling rates [ 43 ]. Two studies indeed revealed a positive effect of masticatory forces on the jaw bone by delaying bone loss following ageing and ovariectomy and by improving the overall jaw bone quality [ 8 , 57 ]. Finally, analysis of the bone surrounding the mandibular M3 showed that Tb.Pf and SMI of the ovariectomized rats increased by 185% and 243.75% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings suggest that reduction of appropriate mastication activity in the growth period results in poor growth of the mandibular condyle. Furthermore conditions simulating aged/postmenopausal status induce atrophy of the mandibular condyle [ 57 ]. In our study, it was observed that OVX caused a significant deterioration of the trabecular bone micro-architecture parameters Tb.Pf and SMI when compared to shOVX.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of functional orthodontics, mastication can activate specific muscular groups, influencing trophism of the bone segment which these muscles are inserted in [1] or originate from [2]. Furthermore, several theories suggest that the stomatognathic apparatus can be meant as an "access door" to the whole body.…”
mentioning
confidence: 99%